Religion in Consumer Society : Brands, Consumers and Markets. - Gauthier, François (Ashgate AHRC/ESRC Religion and Society., 2016)
Presenting an overview of an emerging field in the study of contemporary religion, this book, together with a complementary volume Religion in the Neoliberal Age, explores issues of religion, neoliberalism and consumer society. Claiming that we have entered a new phase that implies more than the recasting of state-religion relations, the authors examine how religious changes are historically anchored in modernity but affected by the commoditization, mediatization, neoliberalization and globalization of society and social life. Religion in Consumer Society explores religion as both shaped by.